Water deoxygenation using a hollow fiber membrane contactor to prevent pipe corrosion for sustainable management of district heating systems: A pilot-scale study. (20th December 2020) - Lee, Jiho; Baek, Soo-Min; Boo, Chanhee; Son, Aseom; Jung, Hoseok; Park, Sung Soo; Hong, Seok Won
Abstract: Dissolved oxygen (DO) is a key factor affecting pipe corrosion in district heating systems (DHS). This study demonstrated effective deoxygenation of water in a DHS using a hollow fiber membrane contactor (HFMC) via systematic investigation from lab-to pilot-scale. First, deoxygenation efficiency was evaluated in a lab-scale HFMC with varying operating parameters including an effective membrane area, flow rate and feedwater temperature. Based on the results from the lab-scale investigation, a pilot HFMC system was designed with capacity of 1 m 3 per day. To achieve a permeate DO concentration below 10 μg L −1 at feedwater temperatures of 20–60 °C, the vacuum degree needed to be lower than the saturated water vapor pressure of 10–120 Torr. In addition, the primary foulant for membrane fouling was organic matter in the make-up and district heating (DH) return water. A significant change in corrosion response was observed for pipe steel in the DHS after deoxygenation. Immersion tests for 14 days indicated that weight loss values had greatly reduced by the deoxygenation process from 39.3 to 1.3 mg cm −2 and from 21.9 to 2.1 mg cm −2 for steel pipe samples immersed in the make-up water and the DH return water of the DHS, respectively. This improved corrosion resistance from deoxygenation was interpreted by electrochemical analysis. As such, this study offers a pilot-scale demonstration of the feasibility of a hollow fiber membrane-based deoxygenation process as an effective tool to prevent the corrosion of steel pipes. Graphical abstract: Image 1 Highlights: DO in water is a key factor affecting pipe corrosion in district heating system. Hydrophobic HFMC successfully reduced DO concentration below 10 μg L −1 . Approximately 96% of coupon weight loss resulted from corrosion was mitigated. Improved corrosion resistance was confirmed by electrochemical analysis.